Novel preparation of anti-static zirconia ceramic by iron infiltration at high temperature. Issue 1 (January 2017) - Yang, Xianfeng; Ni, Zhentao; Xu, Xiewen; Yang, Jianghong
Abstract: A simple and innovative processing method for fabricating anti-static ceramics has been developed based on Fe-infiltration in sintered tetragonal polycrystalline zirconia doped with 3 mol% yttria (3Y-TZP). The 3Y-TZP samples infiltrated by Fe in a reducing atmosphere showed both excellent anti-static and mechanical properties. Effects of infiltration temperature and time on the surface resistivity and Vickers hardness of the prepared samples were investigated. The surface resistivity and hardness were found to decrease with increases in the infiltration time and temperature. For a typical sample infiltrated at 1000 °C for 4 h, the surface resistivity decreased to 10 7 Ω/□, and the Vickers hardness was 11.2 GPa. The microstructure, chemical composition, and anti-static mechanism were investigated by XRD, SEM and XPS. The results indicated that there was a phase transformation from t -ZrO2 to m -ZrO2 during the infiltration process. It was also found that Fe, Fe3 O4 and FeO were located in the infiltration layer, conferring an antistatic property to the ZrO2 ceramics.